Батуринська «Просвіта» у світлі архівно-слідчих справ - Сніжок, З. (Сiверянський лiтопис, 2019)
У статті аналізується архівно-слідча справа особливого відділу 12-ї Червоної армії на членів батуринської «Просвіти», яких було заарештовано за звинуваченням у
створенні нелегальної петлюрівської організації у 1920 р. Матеріали справи містять
інформацію про сфери діяльності Товариства, організацію роботи, чисельний склад,
імена учасників та їхні біографічні дані. Також розглядаються архівно-слідчі справи
1937–1938 рр. на колишніх членів «Просвіти», з метою відстеження їхньої подальшої долі. The issue of activity of the public cultural and educational organization «Prosvita»
Society in Baturyn remains poorly researched. The reason for this is the small number of
archival materials on this topic. It is possible to expand the source base at the expense of
archival investigative cases of the repressive bodies of the communist totalitarian regime
against the members of Baturyn «Prosvita». The article deals with the archival investigative
case of 1920 arrest of members of «Prosvita» in Baturyn on suspicion of creating an illegal
Petliuriv organization. The n ames of 14 members of the Society and their biographical data
are established. The areas of activity of «Prosvita» organization in Baturyn are determined
and traceability of the repressive measures applied by the Bolshevik authorities to the members
of the Society.
Also, the article deals with archival investigative cases of some members of «Prosvita»,
who were repressed in 1937-1938.